AF MIMO Relay Systems with Wireless Powered Relay Node and Direct Link - Li, B.; Rong, Yue (Institute of Electrical and Electronics Engineers, 2018)
IEEE A two-hop amplify-and-forward (AF) multiple-input multiple-output (MIMO) relay system with direct link is considered in this paper. The relay node has no self-power supply and relies on harvesting the radio frequency energy transferred from the source node to forward information from source to destination. In particular, we consider the time switching (TS) protocol between wireless information and energy transfer. We study the joint optimization of the source and relay precoding matrices and the TS factor to maximize the achievable source-destination rate when a single data stream is transmitted from the source node. The optimal structure of the source and relay precoding matrices is derived, which reduces the original problem to a simpler optimization problem. The simplified problem is then solved efficiently by a two-step method. Numerical simulations show that the proposed algorithm yields a higher rate and better rate-energy tradeoff than suboptimal approaches.